(untitled) (Asian Journal of Medical and Biological Research, 2020)
Chronic arsenic toxicity is a severe disease in men and animals which occurs severely in Bangladesh. Arsenic (As) contamination in ground water used in drinking is the major concern because arsenic is present in human and animal food chain. This work was done in quails with a view to observing the efficacy of spirulina (Spirulina platensis) and vitamin E for prevention of arsenic toxicity. 60 quails were used in this study and animals were divided into control group (T0), arsenic treated group (T1), arsenic plus spirulina treated group (T2) and arsenic plus vitamin E treated group (T3). Each group consists of 15 quails. Quails of T0 group were given normal feed and water and kept as control. Quails of T1, T2 and T3 were given 100 mg arsenic trioxide/L drinking water daily for 30 days. In addition to arsenic trioxide quails of group T2 and T3 were simultaneously fed with spirulina @ 1 gm/kg feed and vitamin E @ 400 mg /kg body weight up to 30 days respectively. Five quails from each group (T0, T1, T2 and T3) were sacrificed at 15 days interval in order to determine haematological parameters. Result showed that in group T1, body weight gain was minimum, whereas in group T2 and T3 the body weight gain in quails were better. Reduction of TEC and Hb values were observed in arsenic treated group T1. Whereas in rest groups the TEC and Hb values were comparatively higher than arsenic treated group. Noticeable change observed in liver and kindey of arsenic treated group in compare to the control group. Histopathological changes also observed in liver and kindey of arsenic treated group in compare to the control group. In conclusion, spirulina and vitamin E have significant effect on body weight, hematological and postmortem and histopathological changes. Asian J. Med. Biol. Res. March 2020, 6(1): 93-98